Integration and health care of pupils with special needs in Kaunas schools - GRINIENĖ, Elvyra; BAGDONAS, Antanas; BLIUMBERGIENĖ, Vida (Acta medica Lituanica, 2011)
In recent years Lithuania has been changing its education policies as regards pupils with special needs in agreement with the new legal acts regulating these needs and the ways of meeting them. Aim of the study was to analyse the diversity of disorders of students with special needs who are integrated into general schools of Kaunas and to find their health care possibilities and integration. Methods. The data were collected at 77 Kaunas general schools in the year 2010 on the distribution of pupils by age, the nature of integration and curriculum as well as according to the medical documentation and corrective intervention reports on the health of pupils with special needs. Results. In 2010, all pupils with special needs studied at general secondary schools according to the programmes meeting their potentiality. The number of pupils with special needs is bigger among younger learners. Most pupils had speech and communication disorders; most of them were in primary grades. Other health disorders were typical of pupils with special needs. Their diversity by age was insignificant; more pupils had mental disorders and specific cognition problems, and less suffered chronic disorders. In each school, education and assistance in corrective help to pupils with special needs were provided not only by teachers, but also by special health care professionals. Achievements in improving speech and communication skills reflects well-organized work. Conclusions. Despite achievements in working with pupils with special needs, some problems, such as poor accommodation to the school environment, lack of adapted methodological tools should be solved. Keywords: general secondary school, integrated education, health correction